2010
DOI: 10.5194/acp-10-5573-2010
|View full text |Cite
|
Sign up to set email alerts
|

Aerosols in the tropical and subtropical UT/LS: in-situ measurements of submicron particle abundance and volatility

Abstract: Abstract. Processes occurring in the tropical upper troposphere (UT), the Tropical Transition Layer (TTL), and the lower stratosphere (LS) are of importance for the global climate, for stratospheric dynamics and air chemistry, and for their influence on the global distribution of water vapour, trace gases and aerosols. In this contribution we present aerosol and trace gas (in-situ) measurements from the tropical UT/LS over Southern Brazil, Northern Australia, and West Africa. The instruments were operated on b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(123 citation statements)
references
References 72 publications
6
116
1
Order By: Relevance
“…A comprehensive summary of ultrafine aerosol measurements in the TTL was provided by Borrmann et al (2010) and Weigel et al (2011), based mainly on aircraft campaigns with the M55 Geophysica and DLR Falcon. A key result of these papers is the maximum in particle concentration around 350 K potential temperature, near the main outflow region for deep tropical convection.…”
Section: A Waddicor Et Al: Aerosol In the Tropical Tropopause Layermentioning
confidence: 99%
“…A comprehensive summary of ultrafine aerosol measurements in the TTL was provided by Borrmann et al (2010) and Weigel et al (2011), based mainly on aircraft campaigns with the M55 Geophysica and DLR Falcon. A key result of these papers is the maximum in particle concentration around 350 K potential temperature, near the main outflow region for deep tropical convection.…”
Section: A Waddicor Et Al: Aerosol In the Tropical Tropopause Layermentioning
confidence: 99%
“…Observational evidence suggests that the upper tropical troposphere is one of the most important source regions for the stratospheric particles in the Junge aerosol layer Thomason and Peter, 2006;Borrmann et al, 2010). However, an evaluation of the different mechanisms forming new particles by Lucas and Akimoto (2006) revealed that qualitatively, due to the large uncertainties of parameterizations, NPF was so far inadequately represented in global models.…”
Section: Introductionmentioning
confidence: 99%
“…An important source for stratospheric particles is the tropical tropopause region, where nucleation-mode particles have been observed. Additionally, new particle formation has also been observed in the free troposphere (Brock et al, 1995;Clarke et al, 1999;Borrmann et al, 2010;Weigel et al, 2011). Due to the volatility and the identification of sulfur in collected particles, it was concluded that binary nucleation contributes to (or dominates) the formation of these particles (Brock et al, 1995).…”
Section: Introductionmentioning
confidence: 99%